Molecular characterization of Echinococcus granulosus in south‐eastern Romania: evidence of G1–G3 and G6–G10 complexes in humans. (12th September 2012) - Piccoli, L.; Bazzocchi, C.; Brunetti, E.; Mihailescu, P.; Bandi, C.; Mastalier, B.; Cordos, I.; Beuran, M.; Popa, L. G.; Meroni, V.; Genco, F.; Cretu, C.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract Echinococcus granulosus is the aetiological agent of cystic echinococcosis (CE), which is a public health problem in many eastern European countries, particularly in Romania, where the infection causes a high number of human and animal cases. To shed light on the transmission patterns of the parasite, we performed a genotyping analysis on 60 cyst samples obtained from patients who live in south‐eastern Romania and who underwent surgery for liver or lung CE. DNA was extracted from the endocysts or the cyst fluids, and fragments of cytochrome c oxidase subunit 1 and NADH dehydrogenase subunit 1 mitochondrial genes (cox1 and nd1, respectively) were amplified by PCR and sequenced. We found that most of the samples analysed (59/60) belonged to the G1–G3 complex (E. granulosus sensu stricto), which contains the most widespread and infective strains of the parasite. We also identified the first human patient infected by a non‐G1–G3 genotype of E. granulosus in this country. As the DNA sequence of this cyst sample showed maximum homology with the G6–G10 complex (Echinococcus canadensis), this is, in all likelihood, a G7 genotype, which is often found in pigs and dogs in most countries of eastern and south‐eastern Europe.